Never Brush off Abdominal Pain: A Case of a Grill Brush Bristle Causing Colonic Perforation - Bibek Saha; Vijayvardhan Kamalumpundi; Jenny J. Cao; Crystal H. Kang; Allison Reinhardt; Joelle N. Friesen; Bright Thilagar (Gastro Hep Advances)
Acute abdominal pain constitutes 7% to 20% of all emergency department visits. While abdominal pain encompasses a broad differential, etiologies of enteritis can be divided into 4 major categories, with infection being the most common. We present the first case of enteritis caused by sigmoid colon and possibly jejunal perforation secondary to grill brush bristle ingestion. Despite comprehensive workup for enteritis, the cause remained elusive in our case, necessitating computed tomography enterography, which revealed the foreign body. Clinicians should maintain a high index of suspicion for foreign body ingestion, including grill brush bristle, in cases of unexplained enteritis, as this represents an uncommon but life-threatening etiology.